2021
DOI: 10.18438/eblip29843
|View full text |Cite
|
Sign up to set email alerts
|

Information Seeking Anxiety and Preferred Information Sources of First-Generation College Students

Abstract: Objective – To determine whether information seeking anxieties and preferred information sources differ between first-generation college students and their continuing-generation peers. Methods – An online survey was disseminated at two public college campuses. A total of 490 respondents were included in the results. Independent variables included institution, year in college, and generational status. Instead of using a binary variable, this study used three groups for the independent variable of generational s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 17 publications
(26 reference statements)
0
3
0
Order By: Relevance
“…Likewise, the Nigerian undergraduate students also experienced moderate levels of anxiety while seeking information in the library as reported by Adeeko and Adetimirin (2022). However, the results of Brinkman and Smith (2021) appeared to contradict this finding as they reported lower levels of ISA among first-generation college students. On the other hand, these findings were also supported by the results of Naveed and Mahmood (2019) who found that the business students at the University of Management and Technology, Lahore lacked confidence for advanced levels of information competencies.…”
Section: Discussionmentioning
confidence: 76%
“…Likewise, the Nigerian undergraduate students also experienced moderate levels of anxiety while seeking information in the library as reported by Adeeko and Adetimirin (2022). However, the results of Brinkman and Smith (2021) appeared to contradict this finding as they reported lower levels of ISA among first-generation college students. On the other hand, these findings were also supported by the results of Naveed and Mahmood (2019) who found that the business students at the University of Management and Technology, Lahore lacked confidence for advanced levels of information competencies.…”
Section: Discussionmentioning
confidence: 76%
“…Over half of these investigated stress along with a mental health problem (anxiety and/or depression). Other mental health concerns discussed in the literature were college information seeking anxiety (Brinkman & Smith, 2021), acculturative stress or distress (adapting to the new and different culture of university; Corona et al, 2017; Herrmann & Varnum, 2018), test anxiety (Janke et al, 2017), and homesickness distress (Woosley & Shepler, 2011). Financial anxiety (Potter et al, 2020), financial stress (Cadaret & Rieder Bennett, 2019) and financial distress (Covarrubias et al, 2021; House et al, 2020) were also discussed in FGS.…”
Section: Resultsmentioning
confidence: 99%
“…Eight studies included in the scoping review found that there were no significant differences between FGS and CGS in terms of stress (Holden et al, 2021; Schriver & Teske, 2020; Shields, 2002), stress and depression (Wang & Castañeda‐Sound, 2008), anxiety and depression (Bantjes et al, 2019; Jones & Schreier, 2021), depression (Covarrubias et al, 2020) and college information seeking anxiety (Brinkman & Smith, 2021).…”
Section: Resultsmentioning
confidence: 99%